Human Parvovirus B19 VP2 Empty Capsids Bind to Human Villous Trophoblast Cells in vitro Via the Globoside Receptor - Carole C. Wegner; Jeanne A. Jordan (Hindawi Limited, 2004)
Background: Pregnant women acutely infected with human parvovirus B19 (B19) may transmit the virus to the developing fetus. The mechanism whereby the virus interacts with the placenta is unknown. It is known that globoside receptor is required for successful infection of the target cells, which are the highly undifferentiated, actively dividing colony and burst-form units of the erythroid series. Globoside is present on trophoblast cells which have intimate contact with maternal blood, and may therefore serve as a potential route for B19 transmission into the fetal compartment.